PERANAN PEJABAT PEMBUAT AKTA TANAH BERDASARKAN PERATURAN PEMERINTAH PENDAFTARAN TANAH - Bustomi, Abuyazid (Faculty of Law, University of Palembang, 2020)
Land is a very profitable investment, because its value will never go down, due to natural factors namely population pressure that continues to grow and human needs continue to increase. The Role of Land Deed Officials according to Government Regulation Number 24 of 1997 concerning Land Registration, plays the role of general land deed maker to assist the government through the Land Office in achieving one of the objectives of land registration, namely achieving legal certainty and legal protection for both subjects and objects, to provision of information and for the administration of land administration. If land rights are not registered at the Land office, then the land rights holder will not get a certificate of land rights, where the certificate is a strong proof to provide legal guarantees in the field of land.